2022
DOI: 10.1016/j.crfs.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

What is the link between personality and food behavior?

Abstract: A number of personality characteristics have been linked to various aspects of taste (gustation), trigeminal, and olfactory perception. In particular, personality traits have been linked to olfactory sensory thresholds and olfactory identification abilities, as well as to the sensory-discriminative aspects of taste/flavour perception. To date, much of the research in this area has focused on Sensation Seeking (including Experience Seeking, and Openness to Novel Experiences), with the latter being linked to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 150 publications
(202 reference statements)
0
10
0
1
Order By: Relevance
“…In comparison, there are relatively fewer peer-reviewed journal articles seeking to explain the impact of psychological variables on how consumers perceive their food. While there have been ample amounts of research into individual differences in specific psychological variables, such as food-evoked emotions [9] or personality traits [10,11] in food-related contexts, there is a research gap when looking at how psychological theories of cognitive styles apply to both group and individual differences. These cognitive style theories can encompass many of the more minute psychological variables (e.g., emotional states or responses) and thus offer a great deal of interest into understanding how consumers perceive and behave toward foods.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, there are relatively fewer peer-reviewed journal articles seeking to explain the impact of psychological variables on how consumers perceive their food. While there have been ample amounts of research into individual differences in specific psychological variables, such as food-evoked emotions [9] or personality traits [10,11] in food-related contexts, there is a research gap when looking at how psychological theories of cognitive styles apply to both group and individual differences. These cognitive style theories can encompass many of the more minute psychological variables (e.g., emotional states or responses) and thus offer a great deal of interest into understanding how consumers perceive and behave toward foods.…”
Section: Introductionmentioning
confidence: 99%
“…[ 48 ] A range of Asian‐based diets contain spicy food compared with Western countries; similarly, the prevalence of obesity is as low as 3%, but it is well over 10% in most Western countries. [ 49 ] A large‐scale nationwide Internet data‐based study in China including 212 314 708 individuals reported that dietary preferences ranged by geographical distribution, with higher altitude regions covering large proportions of spicy food; likewise, spicy food appetite was inversely connected to diabetes risk. [ 50 ] Further studies are needed to clarify the interaction between dietary preferences and environmental health.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, subjects consuming a high concentration of sugar solution and a low concentration of sugar solution will also experience different levels of spiciness at the same concentration of capsaicin (Tian et al., 2021). Therefore, food flavor is not a separate sense, but multiple senses built on a complex material basis, mainly including physical senses, chemical senses, and psychological senses (Araujo et al., 2020; Spence, 2022), and current research on food flavor chemistry focuses mainly on chemical senses. Most of the existing literature on food flavor refers to the taste and smell senses produced by various chemical substances, and more in‐depth research is needed for more complex trigeminal senses and their connection to personality traits.…”
Section: Multisensory Flavor Characteristics Of Soy‐based Fermented F...mentioning
confidence: 99%